Emerging evidence for apical dominance in colonial branching Acropora corals - Re, Eleonora; Duarte, Carlos M. (Frontiers in Marine Science, 2025)
Coloniality and clonality in marine sessile organisms offer several advantages, such as better space occupation and directional growth. In coral colonies, species-specific functional connections are maintained among polyps, allowing for resource translocation and colony architecture coordination. A potential whole-colony integration mechanism is apical dominance, a phenomenon controlling branching patterns through hormonal signaling in plants and seagrass, yet unconfirmed in scleractinian corals. This study aims at investigating the occurrence of apical dominance in corals, hypothesizing that highly integrated species exhibit this mechanism. We experimentally tested this hypothesis in situ by removing the apical tip in three different species (Stylophora sp., Acropora hemprichii, A. pharaonis), presenting two contrasting levels of integration and monitoring their branching morphogenesis over time. After 74 days, the null hypothesis that apical dominance does not occur could not be rejected for A. hemprichii and Stylophora sp., likely due to experimental limitations. However, A. pharaonis exhibited accelerated apical regrowth and increased lateral branching after tip removal, suggesting that apical dominance-like mechanisms may operate in this species. These findings highlight the importance of addressing potential Type 1 and Type 2 errors in experimental design to improve reliability while addressing the emergence of apical dominance in highly integrated coral colonies. Further long-term experiments are needed to capture morphometric changes in slow-growing species, such as A. hemprichii. These findings suggest novel endogenous mechanisms coordinating complex three-dimensional morphogenesis in clonal organisms and offer valuable application in the growing field of coral farming and restoration.